إمكانية تطبيق نظام الموازنة على أساس الأنشطة في المصارف - دراسة ميدانية على المصارف الخاصة المدرجة في سوق دمشق للأوراق المالية - (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The purpose of this study is to demonstrate the extent to which private banks listed on the Damascus Stock Exchange can apply modern cost management tools to planning and preparing budgets through the use of ABB. The research focused on the concepts of cost management and the budget system based on the activities and the components of its application, and the availability of these components in private banks. The study was based on descriptive approach, through design of a questionnaire, and distribute it to some employees in private banks listed on Damascus Stock Exchange. The data were analyzed using statistic program SPSS version 20.0. The research found that the fundamentals of applying activity- based budget system are not available in private banks listed on Damascus Stock Exchange, and that private banks do not take into account the application of effective cost management. A number of recommendations were made. يهدف هذا البحث إلى بيان مدى إمكانية تطبيق المصارف الخاصة المدرجة في سوق دمشق للأوراق المالية لأدوات إدارة التكلفة الحديثة في التخطيط وإعداد الموازنات من خلال استخدام نظام الموازنة على أساس الأنشطة (ABB). ركز البحث على بيان مفاهيم إدارة التكلفة ونظام الموازنة على أساس الأنشطة ومقومات تطبيقه، ومدى توافر هذه المقومات في المصارف الخاصة. اعتمد على استخدام المنهج الوصفي من خلال تصميم استبانه وتوزيعها على بعض العاملين في المصارف الخاصة المدرجة في سوق دمشق للأوراق المالية, وتم تحليل البيانات باستخدام البرنامج الإحصائي SPSS الإصدار 20.0، وتوصل البحث إلى أن المقومات الأساس لتطبيق نظام الموازنة على أساس الأنشطة غير متوافرة في المصارف الخاصة المدرجة في سوق دمشق للأوراق المالية، وأن المصارف الخاصة لا تراعي تطبيق إدارة فعالة للتكاليف. وتم تقديم عدد من التوصيات.